A Review On Production Of Bricks From Fly Ash And Palm Oil Fuel Ash As Partial Cement Replacement By Using Cementing Method - Jamil, Nor Halimah; Jamellodin, Dr. Zalipah (Recent Trends in Civil Engineering and Built Environment, 2021)
Brick has been used for a long time and is an important construction material. The conventional construction of bricks has made the raw material such clays come to the depletion of sources. Bricks made of concrete have contributed to the large scale of CO2 emission. The partial replacement of cement as bricks has come as helper in reducing the used of raw material and also the cement. Cement replaced with locally fly ash (FA) and palm oil fuel ash (POFA) has significant potential to address the environment impact, especially in the construction industry by contributing to safe, clean and sustainable production. The physical properties such as the chemical composition and loss of ignition are taken into consideration. To determine the potential of these bricks, compressive test and water absorption value were taken into account at different percentage of FA and POFA used. Based on study, the result shows that, the highest chemical composition in ordinary Portland cement (OPC) calcium oxide (40%-75%), FA is silicon dioxide (30%-60%), POFA silicon dioxide (40%-70%). The loss on ignition in OPC is in range of (0.9%%-3%), FA is in range of (0.1%-6%) and POFA is in (2%-15%) followed the standard requirement. 20% FA content appears to be the optimal mix for the production of bricks. The value of compressive strength for 7 and 28 days of curing shows increment. However, the increase the percentage of FA used the decrease the compressive strength. The compressive strength of POFA indicated the increase the percentage of POFA used, the decrease the compressive strength. Water absorption bricks made of FA increase as the FA percentage used increased. The water absorption of bricks contains POFA also shows increment as the percentage of POFA used is increased.